Vitamin B12 deficiency in the paediatric population. (24th May 2012) - Ruth, ND; Ali, SH; Jayatunga, R
Abstract : Aims: Vitamin B12 deficiency is likely to be more common in the paediatric population than previously recognised. Previous associations of neurodevelopmental status and vitamin B12 deficiency have been well recognised. Our case series of four patients who presented to a NHS Trust, demonstrates a more varied presentation with non-specific manifestations including pancytopaenia, failure to thrive, proteinuria and skin rashes. Methods: 4 children were identified in the last 5 years with a diagnosis of vitamin B12 deficiency (2006-2011). The age range was 11 months to 15 years. Parameters assessed were presenting symptoms, blood results and response to treatment. Results: 3 patients were male, 1 was female. Common feature to all was severe pancytopaenia. All patients complained of malaise, lethargy and had pallor. Associated symptoms were of exertional dyspnoea, chest pain, and excessive weight loss (>10 kg/month). One patient was treated for sepsis, a result of her being neutropenic at presentation. Other clinical manifestations were of severe neuro-developmental regression (with associated cranial MRI findings) and pigmentation in one case. Proteinuria was detected in two cases suggesting a possible genetic cause (Imerslund-Grasbeck Syndrome) which presents with selective vitamin B12 malabsorption with proteinuria. Both the mothers of the two younger cases' (both breastfed), were also found to have vitamin B12 deficiency, thereby suggesting a dietary component. The oldest patient had a good diet, and therefore dietary factors were not felt to contribute. All patients responded to standard treatment with VitB12 injections, with resolution of symptoms. Those due to dietary cause were subsequently treated with oral Vit B12. Conclusion: The common presentation of all four cases was pancytopaenia with its associated complications. 2 cases were found to have a dietary cause. Interestingly one of these was also suspected to have a genetic origin (Imerslund-Grasbeck). A further case was also suspected but testing was declined. The final patient had Juvenile Pernicious Anaemia, as her Intrinsic Factor antibodies were raised. This case series demonstrates the varied presentation and causes of vitamin B12 deficiency, which is commoner than previously acknowledged. It alerts the Paediatricians to be more aware of Vitamin B12 deficiency; especially in children with pancytopaenia.